Hydrothermally extraction of saponin from Acanthophyllum glandulosum root – Physico-chemical characteristics and antibacterial activity evaluation - Roza Najjar-Tabrizi; Afshin Javadi; Anousheh Sharifan; Kit Wayne Chew; Chyi-How Lay; Pau Loke Show; Hoda Jafarizadeh-Malmiri; Aydin Berenjian (Biotechnology Reports, 2020)
Saponin was extracted from Acanthophyllum glandulosum root under subcritical water conditions, and effects of root powder and pH of the solution were evaluated on the concentration of the saponin as manifested in its foamability and antioxidant activity using RSM. FT-IR analysis indicated that A. glandulosum root extract had 2 main functional groups (hydroxyl and amide I groups). Saponin with the highest foam height (4.66 cm), concentration (0.080 ppm) and antioxidant activity (90.6 %) was extracted using 10 g of the root powder and pH value of 4. Non-significant differences were observed between the predicted and experimental values of the extraction response variables. The study demonstrated good appropriateness of resulted models by Response Surface Methodology. Furthermore, higher values of R2 was attained for the foamability (>0.81) and antioxidant activity (>0.97), as well as large p-values (p > 0.05) indication of their lack-of-fit response verified the acceptable fitness of the provided models. The extracted saponin also showed bactericidal effect, which shows potential as a natural antibacterial compound.